2007
DOI: 10.1007/s00508-007-0818-z
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricle diastolic dysfunction in obese patients with newly diagnosed arterial hypertension

Abstract: This study suggests that newly diagnosed arterial hypertension significantly contributes to impairment of left ventricular diastolic function in obese patients before development of structural aberrations detectable on echocardiography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
1
3
0
1
Order By: Relevance
“…The mean values of early mitral inflow velocity (E wave) did not differ significantly in the examined groups. Similar findings in children with hypertension and obesity were observed by Persic et al [23].…”
Section: Discussionsupporting
confidence: 90%
“…The mean values of early mitral inflow velocity (E wave) did not differ significantly in the examined groups. Similar findings in children with hypertension and obesity were observed by Persic et al [23].…”
Section: Discussionsupporting
confidence: 90%
“…Although LV overload is the main factor responsible for LVH in hypertensive patients, LVH does not occur in all hypertensive patients …”
mentioning
confidence: 99%
“…3 Although LV overload is the main factor responsible for LVH in hypertensive patients, LVH does not occur in all hypertensive patients. 4 Other factors may have a role in increasing LV mass in hypertensive patients such as genetic, 5 environmental, 6 and metabolic factors. 7 It was established that the presence of MetS is strongly associated with an increased risk of cardiovascular events, and this risk has been attributed partly to the effect of MetS items on the developing of LVH.…”
mentioning
confidence: 99%
“…Diagnosis of depressed LV ejection fraction carries prognostic implications that alter patient management (10). In obese individuals, echocardiography has been shown to detect alterations of diastolic function in asymptomatic patients referred for bariatric surgery, patients with newly diagnosed arterial hypertension, and patients with obstructive sleep apnea (11,12,13). Some investigators have suggested a staged evaluation of obese patients prior to bariatric surgery with echocardiography performed only in those with baseline electrocardiogram abnormalities such as conduction or ST‐T wave abnormalities (14).…”
Section: Functional Testing For Cad In Extreme Obesitymentioning
confidence: 99%